2016
DOI: 10.1016/j.solener.2016.03.036
|View full text |Cite
|
Sign up to set email alerts
|

Latent heat storage by silica-coated polymer beads containing organic phase change materials

Abstract: Phase change materials (PCMs) are used for latent heat storage. Most promising applications of PCMs are waste heat recovery systems, solar heating systems, building energy conservation systems, and air-conditioning systems. Macroporous poly(ethylene dimethacrylate) (PEDMA) carrier beads were formed by the suspension polymerization technique, imbibed with paraffin or cetyl alcohol phase change materials and coated with a silica shell to prevent their aggregation and the leakage of PCM. PEDMA beads contained 75.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
20
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 45 publications
(25 citation statements)
references
References 22 publications
3
20
0
Order By: Relevance
“…Thes econd weightl oss stage from 150 to 185 8C( % 21.2 wt %) corresponds to the decompositiono fo xygen-containing groups. [50] ForH D, only one weight-loss step,c orresponding to the volatilization of HD,s tarting at approximately 207 8Ca nd ending at about 280 8C, is observed.T his result is similar to the observation of Feczkó et al [47] Similarly, the thermograms of HD/GO and GO-g-HD also exhibit one weight-loss step attributed to the decompositiono fH D. Aw eight loss of 26.2 wt %f or HD/GO occurs in the temperature range of 207-233 8C, and the value for GO-g-HD from 207 to 262 8C is 62.7 wt %. Then egligible weight loss below 150 8Ci ndicates that the two blends are extremely hydrophobic due to the HD covering.…”
Section: Resultssupporting
confidence: 88%
See 3 more Smart Citations
“…Thes econd weightl oss stage from 150 to 185 8C( % 21.2 wt %) corresponds to the decompositiono fo xygen-containing groups. [50] ForH D, only one weight-loss step,c orresponding to the volatilization of HD,s tarting at approximately 207 8Ca nd ending at about 280 8C, is observed.T his result is similar to the observation of Feczkó et al [47] Similarly, the thermograms of HD/GO and GO-g-HD also exhibit one weight-loss step attributed to the decompositiono fH D. Aw eight loss of 26.2 wt %f or HD/GO occurs in the temperature range of 207-233 8C, and the value for GO-g-HD from 207 to 262 8C is 62.7 wt %. Then egligible weight loss below 150 8Ci ndicates that the two blends are extremely hydrophobic due to the HD covering.…”
Section: Resultssupporting
confidence: 88%
“…Figure shows the DSC curves of HD, HD/GO, and GO‐ g ‐HD, and the thermographic data are listed in Table . From the results in Figure , it is revealed that each curve of HD, HD/GO, and GO‐ g ‐HD is composed of one endothermic peak and two exothermic peaks, in agreement with data reported in the literature . The observation of two exotherms upon cooling is due to the long chains of alkanols experiencing two exothermic transitions during crystallization .…”
Section: Resultssupporting
confidence: 88%
See 2 more Smart Citations
“…In comparison with organic PCMs, hydrated salt as inorganic materials has the characteristics of high thermal conductivity, low cost, high energy storage density, and nonflammability. However, phase segregation and supercooling always are the key issues affecting the industrial application of hydrated salts PCMs …”
Section: Introductionmentioning
confidence: 99%